Editorial: The Synergy between School and Family - Błasiak, Anna (Horyzonty Wychowania, 2017)
Family and school are two fundamental educational and socialization environments for the youngest generation. Since the dawn of time, family has been the first and basic place for development and education, and the parents have been the most important carers and educators for their children...